Nuclear Medicine Radiation Dosimetry Advanced Theoretical Principles - McParland, Brian J. (Springer London : Imprint: Springer, 2010)
The field of nuclear medicine is experiencing a transition where accurate dosimetry, approaching that required in external beam radiotherapy, may become the norm. Therapeutic applications are, by nature, patient-specific and bespoke calculations are required. It is becoming increasingly important for nuclear medicine practitioners to be able to administer such precise, carefully calculated doses to their patients, in both the diagnostic and therapeutic settings. Nuclear Medicine Radiation Dosimetry provides a comprehensive account of the theoretical foundations for understanding the dosimetry calculations and internal radiation dosimetry algorithms as applied to both diagnostic and therapeutic nuclear medicine. It elucidates the reader to the theory that underlies the practice, and in doing so, enables more informed judgments and considerations when treating the patient. Written by an authority in the field and laid out for easy consultation, Nuclear Medicine Radiation Dosimetry is an essential reference volume for nuclear medicine physicists in both clinical practice and research. Brian J. McParland, BASc MSc PhD currently heads a commercial medical physics group based in the UK, Norway and India supporting clinical trials developing diagnostic radiopharmaceuticals, vascular contrast media and in vivo optical imaging agents. He is also an elected Fellow of the Canadian College of Physicists in Medicine, the Institute of Physics and Engineering in Medicine, UK and the Institute of Physics, UK.